ANALYSIS OF E-VILLAGE EFFECTIVENESS IN KELURAHAN SADANG SERANG OFFICE, COBLONG DISTRICT, BANDUNG CITY (International Journal of Psychosocial Rehabilitation, 2020)
In this reform era, government commitment and accountability is demanded in the public service sector. The development of information and technology can provide facilities for the government to provide maximum services to the public. The local government has developed E Village. E Village is part of e-government which is useful for serving the management of population. This study aims to examine the effectiveness of the implementation of the e-village. The study was conducted in Sadang Serang Village, Coblong District, Bandung City, Indonesia. The aspects studied related to the implementation of e-village are the effectiveness of brainware, software, hardware, integrated information systems, standard operating procedures, and intellectual property rights, efficiency and increase community participation. The results showed that the effectiveness of the implementation of e-village has shown good results. Despite this, there are still some weaknesses in the implementation of e village such as: there are still data searches done manually, inadequate internet speed, and the inability of the community to access e-village.